A fully implicit conjugate heat transfer method. (1st September 2020) - Mangani, Luca; Darwish, Marwan; Hanimann, Lucian; Al Abed, Ali; Casartelli, Ernesto; Moukalled, Fadl
Abstract: This article deals with the development of an implicit and conservative method for conjugate heat transfer at solid-fluid interfaces. The technique is applicable for both conformal and non-conformal meshes. The method, which is implemented within a fully coupled in-house code, is symmetric in its treatment of the solid and fluid regions and is shown to be very robust for highly complex configurations. To demonstrate the performance of the method, two compressible turbulent conjugate heat transfer test cases, the Mark II and C3X with film cooling, which are benchmarks for simulating the hydrodynamic and thermal fields around and inside turbine blades, are used. Numerical results generated are in good agreement with available experimental measurements.